Career development among women in power a case in male-dominated job - Dayang Nursharida, binti Abang Zakaria (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to determine the career development among women in power who work in male dominated job. It focus on the challenges, competencies and coping strategies of women leader while navigating their career development. This study is done in qualitative approach and used semi-structured interview as data collection method. Three informants participated in this study. The findings then were analyzed using content analysis. Content analysis is used to identify specific themes as a result of an interview. The interviews were transcribed for data analysis purposes. Based on this study, all three specific objectives challenges, competencies and solutions have been identified. The main challenges are stereotype and bias at workplace. Besides, the main competencies identified is personal skill. Apart from that, the main coping strategies support from subordinate/team. The proposed solution method is seen to be able to contribute to those involved in the career planning of women in male-dominated job.